2016
DOI: 10.1007/s11906-016-0676-z
|View full text |Cite
|
Sign up to set email alerts
|

Renal Afferents

Abstract: Purpose of ReviewThe etiology of hypertension, a critical public health issue affecting one in three US adults, involves the integration of the actions of multiple organ systems, including the renal sympathetic nerves. The renal sympathetic nerves, which are comprised of both afferent (sensory input) and efferent (sympathetic outflow) arms, have emerged as a major potential therapeutic target to treat hypertension and disease states exhibiting excess renal sympathetic activity.Recent FindingsThis review highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Excessive sympathetic activity plays crucial roles in the pathogeneses of hypertension, chronic heart failure, and chronic kidney disease ( Fitzgerald, 1983 ; Chen et al, 2015 ; Grassi and Ram, 2016 ; Cheng et al, 2019 ). Renal afferent activity may contribute to the sympathetic overactivity in these diseases ( Esler, 2014 ; Frame et al, 2016 ; Kaur et al, 2017 ). Catheter-based radiofrequency renal denervation (RFRD) was used as a therapy for hypertension, chronic kidney disease, and chronic heart failure ( Veelken and Schmieder, 2014 ; Frame et al, 2016 ; Carlstrom, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive sympathetic activity plays crucial roles in the pathogeneses of hypertension, chronic heart failure, and chronic kidney disease ( Fitzgerald, 1983 ; Chen et al, 2015 ; Grassi and Ram, 2016 ; Cheng et al, 2019 ). Renal afferent activity may contribute to the sympathetic overactivity in these diseases ( Esler, 2014 ; Frame et al, 2016 ; Kaur et al, 2017 ). Catheter-based radiofrequency renal denervation (RFRD) was used as a therapy for hypertension, chronic kidney disease, and chronic heart failure ( Veelken and Schmieder, 2014 ; Frame et al, 2016 ; Carlstrom, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Renal afferent activity may contribute to the sympathetic overactivity in these diseases ( Esler, 2014 ; Frame et al, 2016 ; Kaur et al, 2017 ). Catheter-based radiofrequency renal denervation (RFRD) was used as a therapy for hypertension, chronic kidney disease, and chronic heart failure ( Veelken and Schmieder, 2014 ; Frame et al, 2016 ; Carlstrom, 2017 ). However, the renal denervation therapy destroys both the afferent and efferent renal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic over-activity contributes greatly to the pathogenesis and development of several diseases including chronic kidney disease, chronic heart failure, and hypertension [6]. It has been shown that enhanced renal afferent activity in 2-kidney 1-clip hypertensive mice increases blood pressure and sympathetic nerve activity [49], while renal afferent denervation in the rat prevents the progression of chronic renal failure [50].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the renal nerve contains both afferents and efferents. Chemoreceptors in the kidney can be activated by capsaicin, bradykinin, adenosine, and hypertonic NaCl in the renal tissue and pelvis, while mechanoreceptors mainly respond to changes in pelvic pressure [6]. The renal afferent sensory signals contribute to the sympathetic activation in hypertension and chronic heart failure [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Potential mediators of immune cell infiltration in the kidney are the renal sympathetic nerves, where it is known that their actions in the kidney promote hypertension (18). Renal sympathetic denervation (RDN) is currently in clinical trials for treatment of resistant hypertension in humans (3,7,11). Experiments using RDN in different experimental animal models of hypertension show varying effects on hypertension (1,10,18,24,37).…”
Section: Introductionmentioning
confidence: 99%